Identification of male-biased microRNA-107 as a direct regulator for nuclear receptor subfamily 5 group A member 1 based on sexually dimorphic microRNA expression profiling from chicken embryonic gonads. (5th July 2016) - Miao, Nan; Wang, Xin; Hou, Yue; Feng, Yanping; Gong, Yanzhang
Abstract: Several studies indicate that sexual dimorphic microRNAs (miRNAs) in chicken gonads are likely to have important roles in sexual development, but a more global understanding of the roles of miRNAs in sexual differentiation is still needed. To this end, we performed miRNA expression profiling in chicken gonads at embryonic day 5.5 (E5.5). Among the sex-biased miRNAs validated by qRT-PCR, twelve male-biased and six female-biased miRNAs were consistent with the sequencing results. Bioinformatics analysis revealed that some sex-biased miRNAs were potentially involved in gonadal development. Further functional analysis found that over-expression of miR-107 directly inhibited nuclear receptor subfamily 5 group A member 1 ( NR5a1 ), and its downstream cytochrome P450 family 19 subfamily A, polypeptide 1 ( CYP19A1 ). However, anti-Mullerian hormone ( AMH ) was not directly or indirectly regulated by miR-107. Overall results indicate that miR-107 may specifically mediate avian ovary-development by post-transcriptional regulation of NR5a1 and CYP19A1 in estrogen signaling pathways. Highlights: Sex-biased miRNAs were validated in expression profiles of E5.5 Chicken gonads. Several sex-biased miRNAs might play roles in gonadogenesis through their targets. MiR-107 directly inhibited NR5a1 and CYP19A1 but did not target AMH . MiR-107 specifically regulated ovary-development at post-transcriptional level.